2019
DOI: 10.3389/fpsyg.2019.01115
|View full text |Cite
|
Sign up to set email alerts
|

Economic Circumstances in Childhood and Subsequent Substance Use in Adolescence – A Latent Class Analysis: The youth@hordaland Study

Abstract: The aim of the present study was to investigate the association between longitudinal registry-based data on family income during childhood and self-reported substance use in adolescence, including potential alcohol- or drug problems. Data from the Norwegian population-based youth@hordaland-survey was employed, and the analyzed included n = 8,983 adolescents aged 16–19 years. This information was linked to registry-based information about childhood family income for seven consecutive year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 59 publications
0
13
0
Order By: Relevance
“…Among the nine articles that assessed the relationship between SES changes and child/adolescent health behaviors, three examined adolescent substance use: one in the U.S., one in Norway, and one in Brazil. Together, the three studies suggest that downward income mobility during childhood may be associated with increased alcohol (Poonawalla et al 2014 ), tobacco (Hallal et al 2012 ), or drug use (Skogen et al 2019 ) in adolescence. The Nordic paper also found that adolescents who experienced upward mobility in childhood reported more tobacco and drug usage (Skogen et al 2019 ).…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…Among the nine articles that assessed the relationship between SES changes and child/adolescent health behaviors, three examined adolescent substance use: one in the U.S., one in Norway, and one in Brazil. Together, the three studies suggest that downward income mobility during childhood may be associated with increased alcohol (Poonawalla et al 2014 ), tobacco (Hallal et al 2012 ), or drug use (Skogen et al 2019 ) in adolescence. The Nordic paper also found that adolescents who experienced upward mobility in childhood reported more tobacco and drug usage (Skogen et al 2019 ).…”
Section: Resultsmentioning
confidence: 98%
“…Together, the three studies suggest that downward income mobility during childhood may be associated with increased alcohol (Poonawalla et al 2014 ), tobacco (Hallal et al 2012 ), or drug use (Skogen et al 2019 ) in adolescence. The Nordic paper also found that adolescents who experienced upward mobility in childhood reported more tobacco and drug usage (Skogen et al 2019 ). In contrast, Hallal et al’s ( 2012 ) study in Brazil found upward mobility to be associated with less tobacco.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…As their name suggests, risk conducts put at risk the well-being or the health of the person who engages in them or those in their surroundings. Adolescence is a complex period and, therefore, propitious for these kinds of conducts to arise ( Skogen et al, 2019 ). However, despite the social alarm they generate, in most cases, their appearance during this period is linked to experimenting and, in the same way they appear, they disappear ( Sánchez-Sosa et al, 2014 ; Batllori, 2016 ; Tena-Suck et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%